A Bounding Box-Based Radiomics Model for Detecting Occult Peritoneal Metastasis in Advanced Gastric Cancer: A Multicenter Study - Liu, Dan; Zhang, Weihan; Hu, Fubi; Yu, Pengxin; Zhang, Xiao; Yin, Hongkun; Yang, Lanqing; Fang, Xin; Song, Bin; Wu, Bing; Hu, Jiankun; Huang, Zixing (Frontiers in Oncology, 2021)
Purpose: To develop a bounding box (BBOX)-based radiomics model for the preoperative diagnosis of occult peritoneal metastasis (OPM) in advanced gastric cancer (AGC) patients. Materials and Methods: 599 AGC patients from 3 centers were retrospectively enrolled and were divided into training, validation, and testing cohorts. The minimum circumscribed rectangle of the ROIs for the largest tumor area (R_BBOX), the nonoverlapping area between the tumor and R_BBOX (peritumoral area; PERI) and the smallest rectangle that could completely contain the tumor determined by a radiologist (M_BBOX) were used as inputs to extract radiomic features. Multivariate logistic regression was used to construct a radiomics model to estimate the preoperative probability of OPM in AGC patients. Results: The M_BBOX model was not significantly different from R_BBOX in the validation cohort (AUC: M_BBOX model 0.871 [95% CI, 0.814–0.940] vs. R_BBOX model 0.873 [95% CI, 0.820–0.940]; p = 0.937). M_BBOX was selected as the final radiomics model because of its extremely low annotation cost and superior OPM discrimination performance (sensitivity of 85.7% and specificity of 82.8%) over the clinical model, and this radiomics model showed comparable diagnostic efficacy in the testing cohort. Conclusions: The BBOX-based radiomics could serve as a simpler reliable and powerful tool for the preoperative diagnosis of OPM in AGC patients. And M_BBOX-based radiomics is simpler and less time consuming.